Analisis Manajemen Persediaan dalam Penjualan Sapi Qurban Menjelang Hari Raya Idul Adha : Studi Kasus pada Peternakan Purnomo Sapi Mulyo di Desa Brajan, Boyolali, Jawa Tengah - Muhammad Rafi Ramadhan; Muhammad Syihabuddin (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2026)
This study aims to analyze the inventory management practices of qurban cattle at Purnomo Sapi Mulyo Farm in Boyolali, Central Java, particularly in facing the surge in demand prior to Eid al-Adha. The research is motivated by the unique characteristics of qurban cattle inventory, which involves living assets, seasonal demand, and biological risks that differ significantly from conventional inventory management. A qualitative descriptive approach with a case study design was employed to capture in-depth information regarding inventory planning, procurement, storage, and sales practices. Data were collected through in-depth interviews with the business owner as the key informant, direct observation of operational activities, and documentation review. The findings reveal that inventory management at the farm is conducted in a responsive manner based on consumer orders, enabling the business to minimize overstock risks and operational costs. However, inventory recording remains manual and unstructured, potentially limiting the accuracy of cost calculation and long-term planning. Price fluctuations and supply availability are strongly influenced by the Eid al-Adha momentum, while cattle health and lead time are critical factors affecting inventory effectiveness. From a theoretical perspective, the study extends inventory management concepts to the context of live and seasonal inventory. Practically, the findings suggest that implementing a simple yet structured inventory recording system could enhance operational efficiency and decision-making accuracy in local qurban cattle farms.